Optique moderne et post-moderne dans la composition d'images transculturelles dans trois films de Woody Allen - Nadia Fuchs (Cahiers de Narratologie)
With the recurrent persona of the neurotic and more or less autobiographical Jewish New Yorker, Woody Allen's films have created, willingly or not, their own mythology and a specific genre made up of codes readily accessible to the spectator. However, Woody Allen is more than anything else a postmodern filmmaker who analyses and deconstructs the simulacra of his time. He is thus a conveyor of images which retrace the history of modern art of the XXth and XXIth centuries, and of their strategies of enunciation and reception.